1982
DOI: 10.1007/bf03350475
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thyroid function on submaxillary gland sensitivity to autonomic nervous drugs

Abstract: The effect of changes in thyroid function on the action of autonomic drugs upon the secretion of saliva by the submaxillary glands was studied in male Wistar rats. Hyperthyroidism was induced by the sc administration every 12 h of 10 micrograms/100 g bw of L-triiodothyronine; hypothyroidism was induced by surgical thyroidectomy 2 weeks before the experiments. The dose-response curves to increasing doses of isoprenaline, norepinephrine or methacholine showed in hyperthyroid animals increased salivary secretion,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…This is in consonance with the recently reported presence of 5-HT 4b and 5-HT 7a receptors in the rat submandibular gland (9), both receptor subtypes being coupled to the cAMP pathway (28). We showed previously that thyroid hormones modulate rat submandibular secretion that was stimulated by different agonists (19)(20)(21)(22). This fact and the well-known interaction between thyroid hormones and 5-HT cells (11)(12)(13)(14) prompted us to study the effect of thyroid status upon 5-HT-stimulated amylase secretion in parotid glands.…”
Section: ) and Tri-iodothyroxine (T 3 ) In Experimental And Control Asupporting
confidence: 91%
See 2 more Smart Citations
“…This is in consonance with the recently reported presence of 5-HT 4b and 5-HT 7a receptors in the rat submandibular gland (9), both receptor subtypes being coupled to the cAMP pathway (28). We showed previously that thyroid hormones modulate rat submandibular secretion that was stimulated by different agonists (19)(20)(21)(22). This fact and the well-known interaction between thyroid hormones and 5-HT cells (11)(12)(13)(14) prompted us to study the effect of thyroid status upon 5-HT-stimulated amylase secretion in parotid glands.…”
Section: ) and Tri-iodothyroxine (T 3 ) In Experimental And Control Asupporting
confidence: 91%
“…We showed previously that thyroid hormones modulate rat submandibular secretion that was stimulated by different agonists (19–22). This fact and the well‐known interaction between thyroid hormones and 5‐HT cells (11–14) prompted us to study the effect of thyroid status upon 5‐HT‐stimulated amylase secretion in parotid glands.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The vacuoles that developed in the Medium and High dose T 4 pups are similar to the “watery vacuoles” described in rat parotid gland after strong secretory stimulation (Garrett,1978; Garrett et al,1978). Exogenous thyroxine has been shown to induce hypersecretion by rat salivary glands by means of adrenergic nerve (Tumilasci et al,1982; Medina et al,1984), 5‐hydroxytryptamine (Ostuni et al,2003), substance P (Tumilasci et al,1986a), and vasoactive intestinal peptide (Tumilasci et al,1986b) routes, and indirectly by increased Na+, K+ ‐dependent adenosine triphosphatase activity (Saito et al,1982). The observed appearance of vacuoles and reduction of acinar size thus are most likely due to salivary hypersecretion caused by the induced hyperthyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have indicated that enlarged salivary glands are common in patients with hypothyroidism but this finding is not widely appreciated (1). Most research done on these cases has focused on functional and physiological aspects of thyroid hormones on the gland (2)(3)(4)(5)(6)(7)(8) whilst there has been little work on submandibular gland morphology. The present study describes, using morphometric methods the effects of hypothyroidism on submandibular sali-vary gland structure, including acini (serous and mucous acini), major intralobular ducts (granular and striated ducts), interlobular connective tissue and excretory duct, which lie in the connective tissue (9 -12).…”
mentioning
confidence: 99%